Dyskurs parlamentarny jako przykład wspólnoty komunikatywnej? Obraz parlamentu oczami parlamentarzystów na tle przemian kulturowych (na podstawie "Korpusu dyskursu parlamentarnego" z lat 1918?2021) = Parliamentary discourse as an example of a communicative community? The image of parliament through the eyes of parliamentarians against the backdrop of cultural changes (based on the "Corpus of parliamentary discourse" (CPD) from 1918?2021) - Szczyszek, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work in the team gathered at IPI PAN, which has been ongoing for over ten months, has resulted in the creation of a working (and still further developed) "Corpus of parliamentary discourse". The "Corpus?" was created on the basis of parliamentary transcripts from the years 1918?2021 and already now contains nearly 700 million segments. On this basis, preliminary analytical work on the language of the Polish parliamentarism of the twentieth century is already being conducted.
Keywords: semantyka; leksykografia; leksem; frekwencja leksykalna; Korpusomat; semantics; lexicography; words; lexical frequency